Pengaruh Perputaran Persediaan dan Rasio Perputaran Aktiva Terhadap Return on Invesment Pada PT Gudang Garam Tbk - Anjayani, Nidya Sri; Lutfi, Asep Muhammad; Suhartono, Agus; Sari, Widya Intan; Sunarsi, Denok (TIN: Terapan Informatika Nusantara, 2020)
This study aims to determine the effect of inventory turnover and asset turnover ratio on return on investment at PT. Gudang Garam, Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that inventory turnover has a significant effect on Return on Investment by 94.8%, hypothesis testing is obtained t count> t table or (12.055> 4,350). Asset Turnover Ratio has a significant effect on Return on Investment by 95.5%, hypothesis testing is obtained t count> t table or (13.035> 4,350). Inventory turnover and Asset Turnover Ratio simultaneously have a significant effect on Return on Investment, the regression equation Y = -9,262 + 0,267X1 + 0.073X2 is obtained and the value of determination is 97.0%, hypothesis testing is obtained by the F value> F table or (112.778> 2.770 ).